2016
DOI: 10.1371/journal.pone.0166356
|View full text |Cite
|
Sign up to set email alerts
|

Dressing Wear Time after Breast Reconstruction: A Randomized Clinical Trial

Abstract: BackgroundThe evidence to support dressing standards for breast surgery wounds is empiric and scarce.ObjectiveThis two-arm randomized clinical trial was designed to assess the effect of dressing wear time on surgical site infection (SSI) rates, skin colonization and patient perceptions.MethodsA total of 200 breast cancer patients undergoing breast reconstruction were prospectively enrolled. Patients were randomly allocated to group I (dressing removed on the first postoperative day, n = 100) or group II (dress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
8
0
7
Order By: Relevance
“…Studies in other disciplines support the idea that patients desire simpler wound management after surgery. 18 Furthermore, patients subjectively rated the appearance of scars from wounds covered with HCD higher than those covered with CDD. HCD is suggested to have some intrinsic healing properties, which may help explain the perceived difference in scar appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other disciplines support the idea that patients desire simpler wound management after surgery. 18 Furthermore, patients subjectively rated the appearance of scars from wounds covered with HCD higher than those covered with CDD. HCD is suggested to have some intrinsic healing properties, which may help explain the perceived difference in scar appearance.…”
Section: Discussionmentioning
confidence: 99%
“…. All 10 included studies reported on the surgical site infection in both arms (13,(15)(16)(17)(18)(19)(20)(21)(22)(23). The pooled RR was 0.89 (95% CI: 0.61 to 1.29) (Fig.…”
Section: Surgical Site Infection (Ssi)mentioning
confidence: 99%
“…Patient's perception on comfort. Two studies have reported on the patient's perception on comfort following early or delayed removal of dressing for surgical wounds (21,22). The pooled RR was 0.95 (95% CI: 0.74 to 1.22) (Fig.…”
Section: Surgical Site Infection (Ssi)mentioning
confidence: 99%
“…Nos Quadros 5, 6, 7, 8, 9, 10 e 11, estão apresentadas as sínteses dos estudos incluídos nesta revisão sistemática (BIFFI et al, 2012;DIXON;DIXON;DIXON, 2006;ROBSON et al, 2012;RUIZ-TOVAR et al, 2015;SHEN et al, 2017;STRUIK et al, 2018;VEIGA et al, 2016). Os ensaios estão apresentados de acordo com o ano de publicação.…”
Section: Caracterização Dos Estudosunclassified
“…Quadro 9 -Apresentação da síntese do estudo Veiga et al (2016). Ribeirão Preto, São Paulo, Brasil, 2021.…”
Section: Implicações Para Práticaunclassified